Computational and experimental studies on the development of an energy-efficient drier using ribbed triangular duct solar air heater. (October 2020) - Nidhul, Kottayat; Kumar, Sachin; Yadav, Ajay Kumar; Anish, S.
Highlights: Ribbed triangular duct is proposed for an indirect type solar dryer (ITSD). The new design has 28.78% higher effectiveness compared to ribbed rectangular duct SAH. It exhibits a 60% reduction in moisture ratio for food samples. The average diffusivity coefficient of food samples is enhanced by 93%. For ITSD, ribbed triangular duct SAH exhibits superior performance. Abstract: Triangular duct cross-section is introduced for solar air heater (SAH) of an indirect type of solar dryer (ITSD). Using computational study, the thermo-hydraulic performance of triangular duct SAH with inclined ribs for varying rib inclination (30° < α < 75°) in the turbulent flow regime (5000 < Re < 17500) is studied. With the rib configuration providing maximum thermos-hydraulic performance, a ribbed rectangular duct SAH is designed, and the performance of the same is compared to the former for similar heat input. Results show that the ribbed ( α = 45°) triangular duct has 17% higher effectiveness compared to the latter and 79% when compared to smooth SAH. Ribs in triangular duct solar air heater facilitate the increase in temperature even in the core of the duct, delivering the air at 6 K additional temperature relative to a rectangular ribbed duct for same heat input and flow Re . The superiority of the ribbed triangular SAH is further confirmed by studying the drying characteristics of Okra and two variants of banana, namely Nendran and Robusta for the maximum temperature obtained at the outlet of the respective SAH. Various thin layer drying models available in the literature were analyzed, and Modified page model represented the drying behaviour with R 2 = 0.99. For ITSD, ribbed triangular duct SAH exhibits a maximum of 60.3% reduction in moisture ratio with a maximum increase of 97.9% increase in average values of diffusivity coefficient confirming that it is an energy-efficient design for an ITSD.